Land Reform and Farm Restructuring: What Has Been Accomplished to Date? - Lerman, Zvi (American Economic Review, 1999)
The countries of East Central Europe (ECE) and the former Soviet Union (FSU) entered the transition in 1989–1990 with a common heritage in agriculture: most land, regardless of its ownership, was cultivated collectively in large-scale farms with thousands of hectares and hundreds of member-workers; the commercial production from the collective sector was supplemented by subsistence-oriented individual agriculture based on rural household plots of less than one hectare; product markets and input supply channels were largely controlled by state organizations within an administrative command framework; budget constraints virtually did not exist. The persistent inefficiency of socialized agriculture was usually attributed to collective production, which is rare in countries with a marketoriented economy, and to farm sizes that were too large compared to the observed market ‘‘best practice.’’ The strategy of agricultural transition formulated in the early 1990’s accordingly envisaged a transformation from collective to individual agriculture as the ultimate goal. Individual farmers could form associations to ensure efficient farm services and engage in land transactions to achieve optimal farm sizes. Pragmatic considerations suggested an intermediate stage involving transition to downsized but still relatively large corporate or cooperative farms based on private ownership of land and assets and with radically modified, profit-motivated management.